VARIATION IN VEGETATION COVER OF SHRUB AS A VEGETATION CANDIDATE FOR GREEN OPEN SPACE COMPONENT IN CEMPAKA SUBDISTRICT, BANJARBARU - Rahmani, Dienny Redha; Gunawan, Gunawan; Peran, Setia Budi (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Good urban structure and activity require green open space to improve the ecological functions in it, but trees are not fully able to meet the important space in the urban vegetation while woody shrubs have the potential for it. Therefore, the objective of this study was to find out the potential of shrub as the component of urban vegetation so that it can be used as the information regarding the planning for land conversion in Cempaka subdistrict. Three sampling stations with 3 plots of 4x4 m at each station were determined on the basis of green open space data of shrubs in Cempaka subdistrict using a purposive sampling method. The shrub canopy was analyzed and environmental parameters were measured. Data were analyzed using the analysis of canopy volume, Pearson correlation analysis and analysis of Importance Value Index (IVI). The results of shrub vegetation estimation indicated that the volume of shrub vegetation canopy in Cempaka subdistrict was up to 22,462,878.50 m3 while the area with shrubs in the subdistrict was 5,675.116 hectares. Pearson correlation analysis showed that the canopy volume of shrubs in Cempaka subdistrict affected the changes in environmental factors. The most dominant shrub species was Ficus fistulosa Reinw. ex Bl with IVI value of 56.1%. It can be concluded that shrubs have potential as the component of the green space vegetation in urban areas.